Characterisation and mechanical properties of unsaturated polyester/acrylated epoxidised palm oil polymer blend at different acrylated epoxidised palm oil processing method - Nur Bazilah, Thalib; Siti Noor Hidayah, Mustapha; K. F., Chong (IOP Publishing, 2018)
Acrylated epoxidized palm oil (AEPO) prepared by the reaction of epoxidized palm oil (EPO) with acrylic acid, triethylamine initiator and hydroquinone inhibitor. The acrylated epoxidised palm oil (AEPO) was prepared at various temperature and reaction times. The unsaturated polyester (UPE) resin was blended thoroughly with 10 wt% of the synthesised acrylated epoxidised palm oil (AEPO) at room temperature, and thermally cured at 100 ℃ and post-cured at 160 ℃. The prepared palm oil derivative was characterised by using Fourier Transform Infrared (FTIR). The cured polymer blend was characterised by tensile test, impact test and thermal gravimetric analysis. The FTIR test proved the formation of acrylate functional group in acrylated epoxidised palm oil (AEPO) with characteristic absorbance at 1600-1600 cm-1 that indicates C=C functional group of the acrylate. The polymer blend tensile strength of the palm oil acrylate processed at 110 ℃ for 16 hours (M2) showed reduction from 25.56 MP to 13.26 MP (48%), reduction in tensile modulus from 1.47 GPa to 1.18 GPa (19.7%) and the highest impact strength among the four acrylates of polymer blend is 21.97 J/m from palm oil acrylate processed at 105 ℃ for 16 hours (M3). However, polymer blend from M2 acrylate showed increased in elongation at break from 2.805 % to 3.493 % (24.5 %) compared to neat unsaturated polyester. The lowered mechanical properties of unsaturated polyester/acrylated epoxidised palm oil (UPE/AEPO) blend were caused by the present of stiff palm oil derivative and failure of acrylated epoxidised palm oil (AEPO) to crosslink with unsaturated polymer. However, the increased elongation at break outweighed reduction in tensile and impact of the polymer blend